A Case for Using Electronic Health Record Data in the Evaluation of Produce Prescription Programs - Ronit A. Ridberg; Amy L. Yaroch; Nadine Budd Nugent; Carmen Byker Shanks; Hilary Seligman (SAGE Publishing, 2022)
Produce prescription programs within clinical care settings can address food insecurity by offering financial incentives through "prescriptions" for fruits and vegetables to eligible patients. The electronic health record (EHR) holds potential as a strategy to examine the relationship between these projects and participant outcomes, but no studies address EHR extraction for programmatic evaluations. We interviewed representatives of 9 grantees of the U.S. Department of Agriculture's Gus Schumacher Nutrition Incentive Grant Program's Produce Prescription Projects (GusNIP PPR) to understand their experiences with and capacity for utilizing EHR for evaluation. Five grantees planned to use EHR data, with 3 main strategies: reporting aggregate data from health clinics, contracting with external/third party evaluators, and accessing individual-level data. However, utilizing EHRs was prohibitive for others due to insufficient knowledge, training and/or staff capacity; lack of familiarity with the Institutional Review Board process; or was inappropriate for select target populations. Policy support for produce prescription programs requires a robust evidence base, deep knowledge of best practices, and an understanding of expected health outcomes. These insights can be most efficiently and meaningfully achieved with EHR data, which will require increased financial support and technical assistance for project operators.